"Getting ready to teach": using photovoice within a collaborative action research project. Issue 1 (1st January 2021) - Wai-Yan Wan, Sally; Chu, Carson Ki-Wing; Cheng, Angus Ho-Hei; Hui, Elim Sein-Yue; Fung, Ken Chun-Kit; Yu, Howard Hoi-Wik
ABSTRACT: The paper draws upon a collaborative action research project using Photovoice aiming at empowering participants to voice and critically reflect by thinking deeply about their context and difficulties, and using images to foster critical consciousness. Nineteen prospective teachers in a Hong Kong public university participated in this collaborative action research project. Findings highlight the obstacles and concerns that prospective teachers faced, core reflections, and action plans for overcoming such challenges. This study demonstrates the feasibility of using Photovoice to facilitate reflective dialogues in developing professional teachers in initial teacher education.